(untitled) - Clifford, Donald K. (Toronto, 1985)
A report on the impact of America's successful midsize corporations explains how other companies from the Fortune 500 corporations to small businesses can adapt to the strategies of these midsize companies for success.
Keywords: Industrial management,Quản trị công nghiệp; Hoa Kỳ; United states,United states